Comparative study on risk for birth defects among infants after in vitro fertilization and intracytoplasmic sperm injection. (2nd January 2019) - Zhu, Jing; Zhu, Qianqian; Wang, Yun; Wang, Bian; Lyu, Qifeng; Kuang, Yanping
ABSTRACT: This large retrospective study was conducted to compare the risk for birth defects among infants conceived by in vitro fertilization (IVF) with that among infants conceived by intracytoplasmic sperm injection (ICSI) and to explore the effect of frozen embryo transfer (FET) on the risk for birth defects among infants born by IVF and ICSI. All patients who received assisted reproductive technology (ART) treatment and who underwent childbirth during the period January 2005–August 2017 were included in this study. There were 18, 221 births after ART included in the analysis; of these births, 12, 649 were conceived by IVF, and 5, 572 were conceived by ICSI. In the study, the prevalence of any birth defect in singleton infants was 1.15% with the use of IVF and 1.38% with the use of ICSI, and that in twin infants increased to 2.74% by IVF and 2.58% by ICSI. However, no significant difference between IVF and ICSI was found among all infants, singleton births or twin births. Additionally, in assessing ART infants born after FET, we did not detect a difference in the risk for birth defects between infants born by IVF and those born by ICSI. These results indicate that among the entire cohort of children conceived from ART and among the children conceived from FET, the risk for birth defects after ICSI is similar to that after IVF.Abbreviations: IVF: in vitro fertilization; ICSI: intracytoplasmic sperm injection; FET: frozen embryo transfer; ART: assisted reproductive technology; ET: embryo transfer; BMI: body mass index; OHSS: ovarian hyperstimulation syndrome; CMOH: Chinese Ministry of Health; ICD-10: International Classification of Diseases, 10 th edition; PTB: preterm birth; OR: odds ratio; aOR: adjusted odds ratio; CI: confidence interval